Em busca do hidrograma ecológico para a planície de inundação do alto rio Paraná : considerações iniciais. - Okawa, Cristhiane Michiko Passos (2009)
The study area is an Protected Area, with a floodplain containing heterogeneity of habitats and high biodiversity. The existence of reservoirs cascade above the study area promotes a strong regularization of the natural flow, causing changes in abiotic characteristics and in the structure and integrity of biotic communities, reducing the local biodiversity. The natural regime paradigm dictates that there is a flow regime, existing before the occurrence of significant changes due to anthropogenic activities, capable of maintaining the health of a river. From the natural flow regime and the magnitude, duration, frequency, timing and the rate of change of the ecologically relevant flows, it is possible to find an initial environmental flow that assembled some hydrological aspects. Therefore, in Chapter I, there is a review of concepts that, over time, changed and led to the definition of the environmental flow concept; some of the Brazilian legislation on water grant and some methods and issues that help the development of the environmental flow. In Chapter II, the goal is generate hydrological subsidies for the construction of the environmental flow for the research. For this, it was determined the changes on the flow regime after the construction of the reservoir cascade, especially after the hydroelectric power plant operation in Porto Primavera, and to relate this changes with some ecological implications. In Chapter III, based on the information obtained in Chapter II, the ecological natural flows were determined and the initial environmental flow was found based on the hydrological aspects. This initial environmental flow should be widely discussed by the researchers who study the floodplain, and other aspects should be considered at finding the final environmental flow. The environmental flow can guide the effective water resource management in a way the water management is promoted to meet the human needs and protect the ecological integrity of the ecosystem.